First do the translation: you want to "move" x and y so that x= 3/8, y= 3/2 is moved to 0, 0. Do that by taking u= x- 3/8 and v= y- 3/2. Then x= u+ 3/8, y= v+ 3/2, x'= u, y'= v', and so the equations become and [tex]y'= v'= -4(u+ 3/8)+ (v+ 3/2)= -4u+ v.

Now there are two, equivalent and very similar, ways to continue. The first is to recognize that the first equation is non-linear because of the " ". The only way to "linearize" that is to drop the : u'= -2u+ 2v and v'= -4u+ v. The "translated matrix" is .

The other way is to form the "Jacobian". If and the Jacobian is

In this case that would be [tex]\begin{bmatrix} . Now let u and v be 0 which gives the same matrix as before. This second method is more "formal" and helps determine how to "linearize" a formula.